A walk in the PARC: developing and implementing 21st century chemical risk assessment in Europe - Marx-Stoelting, P; Rivière, G; Luijten, M; Aiello-Holden, K; Bandow, N; Baken, K; Cañas, A; Castano, A; Denys, S; Fillol, C; Herzler, M; Iavicoli, I; et al. (Archives of toxicology, 2023)
Current approaches for the assessment of environmental and human health risks due to exposure to chemical substances have served their purpose reasonably well. Nevertheless, the systems in place for different uses of chemicals are faced with various challenges, ranging from a growing number of chemicals to changes in the types of chemicals and materials produced. This has triggered global awareness of the need for a paradigm shift, which in turn has led to the publication of new concepts for chemical risk assessment and explorations of how to translate these concepts into pragmatic approaches. As a result, next-generation risk assessment (NGRA) is generally seen as the way forward. However, incorporating new scientific insights and innovative approaches into hazard and exposure assessments in such a way that regulatory needs are adequately met has appeared to be challenging. The European Partnership for the Assessment of Risks from Chemicals (PARC) has been designed to address various challenges associated with innovating chemical risk assessment. Its overall goal is to consolidate and strengthen the European research and innovation capacity for chemical risk assessment to protect human health and the environment. With around 200 participating organisations from all over Europe, including three European agencies, and a total budget of over 400 million euro, PARC is one of the largest projects of its kind. It has a duration of seven years and is coordinated by ANSES, the French Agency for Food, Environmental and Occupational Health & Safety.
Keywords: Exposure assessment; Risk Assessment; Evropa; Chemicals; Hazard characterisation; Human biomonitoring (HBM); Next-generation risk assessment (NGRA); Safety assessment; hodnocení rizik; Humans; Europe; lidé; New approach methods (NAM)